Evaluation of probiotic effects on physiological parameters in healthy and stressed broilers - Negm, Eman A.; Darwish, Madeha H.A. (Journal of Advanced Veterinary Research, 2026)
Clarifying the impact of probiotics on healthy and transported stressed broilers was the goal of the current study. Two hundred and ten male broiler chicks, 1-day-old were split up into 3 groups in 7 pens, each 10 broilers: a standard feed combined with the probiotic, Bacillus subtilis PB6, control (C), lower dose 0.25 (L), and higher dose 0.5 (H) g/kg feed for 35 days. At the conclusion of the study, 5 birds per group were taken for blood collection. Besides, another 5 birds per group were driven for 80 kilometers (km) and then taken for blood collection. The findings indicated that probiotic exposure had an improvement effect on serum lipid profiles, liver enzymes, oxidative markers and some biochemical parameters of both healthy C and stressed (S) broilers. Both L and H dose of probiotic significantly decreased low density lipoprotein (LDL), very low-density lipoprotein (VLDL), triglyceride (TG), total cholesterol (TC), uric acid (UA), glucose, alanine aminotransaminase (ALT), aspartate aminotransaminase (AST), malonaldehyde (MDA) and creatine kinase (CK) while significantly increased high-density lipoprotein (HDL) and total antioxidant capacity (TAC) in comparison with both C and S broilers groups. Besides, stressed broilers treated by lower and higher probiotic doses (LS and Hs, respectively) revealed a marked rise in serum albumin level in comparison with S group while albumin didn't show significant change comparing L and H groups with the C one. Overall, this study approved that administration of probiotic in a higher dose 0.25 g/kg had a better effect in improving health and decrease stress side effects than that in the lower dose 0.25 g/kg feed.